2016
DOI: 10.3389/fpsyt.2016.00183
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Effects on Athletes’ Cognitive Performance: An Exploratory Proof of Concept Trial

Abstract: Among the 2016 Olympic and Paralympic Games’ unforgettable moments, one could not overlook performances by Phelps and Bolt, which challenge old premises about the maximum extension of individual supremacism in ultracompetitive modalities and the doping scandals. Different media channels resonated these two trends, with an unseen rise on discussions about traits and practices that may set ultrahigh performance athletes apart from the more ordinary ones. Yet, some key issues remain undebated. This paper aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…Elite athletes may also use substances for relief of stress, negative emotions, pain, cravings and withdrawal 345 424. Athletes may use ergogenic substances,425 doping methods such as gene doping426 427 and blood transfusions,428 and neuromodulation (eg, transcranial stimulation) 429 430. Further, athletes may unwittingly ingest ergogenic substances by taking dietary substances that contain adulterants 431.…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…Elite athletes may also use substances for relief of stress, negative emotions, pain, cravings and withdrawal 345 424. Athletes may use ergogenic substances,425 doping methods such as gene doping426 427 and blood transfusions,428 and neuromodulation (eg, transcranial stimulation) 429 430. Further, athletes may unwittingly ingest ergogenic substances by taking dietary substances that contain adulterants 431.…”
Section: Specific Mental Health Symptoms and Disorders In Elite Athletesmentioning
confidence: 99%
“…This improvement was not accompanied by a reduction in the RPE. Meanwhile, Borducchi et al [14] found an improvement in cognitive performance and mood in elite athletes of different sport modalities (n = 10) after ten days of anodal stimulation over the left dorsolateral prefrontal cortex, which, according the authors, may contribute to performance gains, greater well-being and faster recovery. However, due to the lack of a control condition (Borducchi et al) and small sample sizes in their studies (like in almost every previous study on tDCS and sport performance), the above results should be considered with caution.…”
Section: Introductionmentioning
confidence: 99%
“…With the brain being the central organ to many features that individuals would like to improve, neuroenhancement would attract a lot of interest. Sports players can use it to gain an advantage over other competitors; students will be able to use it to perform better in tests; and the military can use it to gain an advantage over other countries ( Fregni et al , 2005 ; Borducchi et al , 2016 ). Alternatively, an argument can be made for professionals such as doctors who work in high-pressure environments to have access to this technology.…”
Section: Neurotechnology: the Good And The Badmentioning
confidence: 99%